Seasonal Dynamics of Tropical Forest Vegetation in Ngoc Linh Nature Reserve, Vietnam Based on UAV Data (Forest and Society, 2021)
Seasonal dynamics in tropical forests are closely related to the variation in forest canopy gaps. The canopy gaps change continuously in shape and size between the rainy and dry seasons, leading to the variation in the vegetative indicators. To monitor the variation of the canopy gaps, UAVs were used to collect datas in the mentioned tropical forests at an altitude of over 1,000m in Ngoc Linh Nature Reserve, Vietnam with a post-processing image resolution of about 8cm, which allows the detection of relatively small gaps. The analysis results at 10 squares of 1 ha showed a decrease in the area of ​​ canopy gaps from the rainy season in September 2019 to the dry season of May 2020. The mixed broad-leaved or broadleaf forest dominates with a greater variation, when the area of ​​the gaps decreases significantly. The variation in forest canopy gaps and vegetative indicators are closely related to the high differentiation of terrain, the seasonal and the dry season climatic characteristics. The fluctuation of the vegetation cover affects the habitats of the species under the forest canopy such as animals, birds and soil fauna. This is one of the scientific bases that contributes to the management and conservation of flora and fauna biodiversity, especially in mountainous tropical forests such as Ngoc Linh Nature Reserve.
Keywords: Canopy gaps; drone; seasonal variation; Triangular Greenness Index (TGI); tropical forest